Pigeons combine compass and landmark guidance in familiar route navigation. - Biro, D; Freeman, R; Meade, J; Roberts, S; Guilford, T (2007)
How do birds orient over familiar terrain? In the best studied avian species, the homing pigeon (Columba livia), two apparently independent primary mechanisms are currently debated: either memorized visual landmarks provide homeward guidance directly, or birds rely on a compass to home from familiar locations. Using miniature Global Positioning System tracking technology and clock-shift procedures, we set sun-compass and landmark information in conflict, showing that experienced birds can accurately complete their memorized routes by using landmarks alone. Nevertheless, we also find that route following is often consistently offset in the expected compass direction, faithfully reproducing the shape of the track, but in parallel. Thus, we demonstrate conditions under which compass orientation and landmark guidance must be combined into a system of simultaneous or oscillating dual control.